Spectral analysis of asteroids distribution on semimajor axis. LS-method - Черкас, Юрий Васильевич; Коломиец, Светлана Владимировна; Волощук, Юрий Иванович (Technology audit and production reserves, 2013)
Existing methods of the analysis of distributions of orbits of small bodies of the Solar system for the presence of periodic components are based on the construction of the corresponding histograms of the number. In the case when the analyzed data contain a powerful systematic component (trend), and a required signal, if present, has low power in comparison with a random component, the detection of a useful signal becomes a difficult task. To avoid errors such as false signal detection, the additional use of the analysis of distributions of orbits without creation of histograms of the number is proposed in the paper. The method is based on the analysis of variation series of the density of orbits in the sample sorted by the analyzed parameter. Thus, the specified series, unlike the similar one obtained in the creation of histograms, is uneven that, respectively, imposes constraints on a choice of the method of the spectral analysis. The research of a sample of NEA (near-Earth asteroids) orbits by both methods and their comparative analysis are given in the paper.